2021
DOI: 10.1038/s41419-021-03644-5
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of specific donor-dependent variations of mesenchymal stem cells in immunomodulation to enhance therapeutic values

Abstract: Mesenchymal stem cells (MSCs) are one of the most widely clinically trialed stem cells, due to their abilities to differentiate into multiple cell lineages, to secrete regenerative/rejuvenative factors, and to modulate immune functions, among others. In this study, we analyzed human umbilical-cord-derived MSCs from 32 donors and revealed donor-dependent variations in two non-correlated properties, (1) cell proliferation, and (2) immune modulatory functions in vitro and in vivo, which might explain inconsistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…The proliferation rate of BV2 cells was detected after co-culturing with the 32 lines of hUCMSCs culture medium. The results showed that different lines of hUCMSCs had different inhibitory abilities to the proliferation of BV2 cells ( Zhang et al, 2021 ). We chose line #22 with a strong inhibitory ability (i.e., MSC_A), line #20 with a weak inhibitory ability (i.e., MSC_C), and line #27 with a moderate inhibitory ability (i.e., MSC_B) for the subsequent experiments ( Figures 1B,C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proliferation rate of BV2 cells was detected after co-culturing with the 32 lines of hUCMSCs culture medium. The results showed that different lines of hUCMSCs had different inhibitory abilities to the proliferation of BV2 cells ( Zhang et al, 2021 ). We chose line #22 with a strong inhibitory ability (i.e., MSC_A), line #20 with a weak inhibitory ability (i.e., MSC_C), and line #27 with a moderate inhibitory ability (i.e., MSC_B) for the subsequent experiments ( Figures 1B,C ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we found that hUCMSCs from different donors (e.g., mothers) showed different inhibitory abilities for BV2 cell proliferation ( Zhang et al, 2021 ). We selected three cell lines that had strong, general, and weak inhibition to BV2 cell proliferation, labeled as line A of human umbilical cord-derived mesenchymal stem cell (MSC_A), line B of human umbilical cord-derived mesenchymal stem cell (MSC_B), and line C of human umbilical cord-derived mesenchymal stem cell (MSC_C), and hypothesized that the hUCMSC line that had a strong inhibition to BV2 cell proliferation would have a greater therapeutic effect on SCI than the other lines through inhibition of the microglia-mediated inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to highlight that our process was based on the use of an UC collected from a single donor. However, inter-donor heterogeneity has already been reported and may influence the therapeutic effect of MSC-based therapies leading to treatment failure [ 30 ]. In order to address this issue, our perspective is to first assess and compare UC-MSC properties and biological activities between several donors and to define specifications allowing to identify the best donors.…”
Section: Discussionmentioning
confidence: 99%
“…However, inter-donor heterogeneity has already been reported and may in uence the therapeutic effect of MSCs-based therapies leading to treatment failure (30). In order to address this issue, our perspective is to rst assess and compare UC-MSCs properties and biological activities between several donors and to de ne speci cations allowing to identify the best donors.…”
Section: Discussionmentioning
confidence: 99%